Differences in D-Dimer Levels in Acute Ischemic and Hemorrhagic Stroke: Observational Study in the Emergency Department of Dr. M. Djamil General Hospital, Padang, Indonesia - Yunus, Dyniyah; Elfira Yusri; Desywar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Stroke is the second largest cause of death worldwide with a high morbidity rate of up to 50% of survivors get chronic disability. Rapid diagnosis in patients with suspected acute ischemic or hemorrhagic stroke is very important to determine management and prognosis. D-dimer is an indirect marker of fibrinolysis which functions as a significant marker of activation of coagulation and fibrinolysis. This study aims to determine the differences in D-dimer levels in ischemic and acute hemorrhagic stroke patients in the emergency room (ER) of Dr. M. Djamil General Hospital Padang. Methods: Analytical observational research by cross-sectional design was carried out on 56 samples consisting of 28 acute ischemic and 28 acute hemorrhagic stroke samples for the period December 2022-June 2023. D-dimer levels and CTscan checked on each group and analysis is carried out. Results: The most common characteristics of research subjects were men, namely 35 patients (62.5%) and aged 51-60 years (32.1%). The mean D-dimer levels for ischemic and hemorrhagic strokes were 794.33 ng/mL (±2.63) and 1288.25 ng/mL (±2.51) with a p-value = 0.055. Conclusion: The mean D-dimer in acute hemorrhagic stroke was higher than in acute ischemic stroke but there was no statistically significant difference. The D-dimer examination cannot differentiate the type of stroke that occurred.